Dynamic social alignment on operational level and organisational performance - Levkov, Nikola (Inderscience Publishers, 2018)
Business-IT (BIT) alignment on different organisational levels is thought to facilitate organisational performance. This study investigates how dynamic social alignment on an operational level improves organisational performance. The concept of dynamic social alignment has been introduced based on the theory of dynamic capabilities and the integration of two constructs: IS change agreement and task support satisfaction (TSS). The business value of dynamic social alignment was measured through business process performance and organisational performance. A conceptual model was thus developed and empirically validated through structural equation modelling (SEM). It is confirmed in this study that organisations which have better dynamic social alignment on the operational level continuously support the execution of changing everyday business tasks. The results also confirmed the mediating role of business process performance between task support satisfaction (TSS) and organisational performance. The study reveals that business and IT professionals need to nurture and maintain dynamic mutual agreement regarding IS changes in order to improve performance. In this manner, their organisation would be more prepared for reconfiguration and transformation, vital for adjustment to rapidly changing environment
Keywords: business-IT alignment; dynamic social alignment; IS change agreement; shared understanding; task support satisfaction; TSS; business process performance; organisational performance; IT business value.